La Patrimonialisation de l’héritage minier dans le Nord-Pas-de-Calais : un outil efficace de réconciliation de la population locale avec son passé ? - Camille Mortelette (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In 2012, the Nord-Pas-de-Calais mining basin became a UNESCO World Heritage Site as a “living, evolving cultural landscape”. This inscription is presented as the culmination of a process of patrimonialisation wich had begun in the 1990s. The speeches of the heritage actors regularly evoke the possibility of a “return of pride” for the inhabitants of the territory thanks to this inscription. Indeed, like the Louvre Lens, it is associated with institutional recognition for the local population and aims to bring about reconciliation between the population and an heritage that has long been discredited. However, does this Unesco inscription have only entirely positive effects for these inhabitants? Based on thesis work completed in 2019, this article seeks to demonstrate that despite the measures that are readily described as encouraging participation by the inhabitants, the heritage process that has been initiated is still essentially institutional and top-down. It also points out that, despite the fact that most inhabitants value the inscription, it also brings constraints in their daily spatial practices and ambiguities in the renewal of the territorial representations it proposes.